Social Media and the Surgeon - Margolin, David A. (Clinics in Colon and Rectal Surgery, 2013)
As the Internet has matured, social media has developed and become a part of our everyday life. Whether it is Facebook, YouTube, or LinkedIn, we now communicate with each other and the world in a very different manner. As physicians, and specifically colon and rectal surgeons, it is important that we understand this new technology, learn its limitations, and utilize it to foster growth of our practice, trade, and potentially result in better patient care.
Keywords: social media; Facebook; YouTube; LinkedIn